2019
DOI: 10.1186/s13287-019-1285-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a promotes bone regeneration in irradiated bone defects by enhancing osteoblastic differentiation of mesenchymal stromal cells in rats

Abstract: Background Radiation exposure negatively affects the regenerative ability and makes reconstruction of bone defects after tumor section difficult. miR-34a is involved in radiation biology and bone metabolism. The aim of this study was to investigate whether miR-34a could contribute to bone regeneration in irradiated bone defects. Methods The expression of miR-34a was analyzed during the osteoblastic differentiation of irradiated BMSCs and bone formation in irradiated bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…It has been confirmed that the abnormal expression of miRNAs is closely related to stem cell differentiation [37]. For instance, miR-34a, miR-450a-5p, and miR-28- 5p have been revealed to be involved in regulating the osteoblastic differentiation of mesenchymal stem cells [38,39]. In BMSCs, the adipogenic and osteogenic differentiation can also be regulated by miR-383 [40], miR-20a-5p [41], and miR-20a-5p [41].…”
Section: Discussionmentioning
confidence: 92%
“…It has been confirmed that the abnormal expression of miRNAs is closely related to stem cell differentiation [37]. For instance, miR-34a, miR-450a-5p, and miR-28- 5p have been revealed to be involved in regulating the osteoblastic differentiation of mesenchymal stem cells [38,39]. In BMSCs, the adipogenic and osteogenic differentiation can also be regulated by miR-383 [40], miR-20a-5p [41], and miR-20a-5p [41].…”
Section: Discussionmentioning
confidence: 92%
“…With regard to skeletal disease treatment, agomiR-130a intravenously injection reduces bone loss in elderly mice by targeting Smurf2 and Pparγ genes [ 137 , 138 ], while collagen-based hydrogel containing agomir-34a elevates bone volume in mouse radiational bone injury area by downregulating Notch1 expression in BMSCs [ 139 ]. In addition, miR-328 is the antagonist of Axin1 gene, whose product AXIN1 protein is an inhibitor of Wnt signaling pathway.…”
Section: Application Of Epigenetic Regulation In Skeletal Diseasesmentioning
confidence: 99%
“…6 In another independent study, Liu et al found that miR-34a promotes bone regeneration in irradiated bone defects by enhancing osteoblastic differentiation of BMMSCs in rats. 7 In contrast, Bléry et al reported that the addition of a high concentration of…”
Section: Introductionmentioning
confidence: 96%